Frank Capra's It's a wonderful life [videorecording (DVD)] - Capra, Frank, 1897-1991; Stewart, James, 1908-1997; Reed, Donna, 1921-1986; Barrymore, Lionel, 1878-1954; Stern, Philip Van Doren, 1900-1984 (Paramount Pictures : Paramount Home Entertainment, 2006)
A man is saved from a suicide attempt by an angel and is then shown how important he is to the people who love him. A Christmas classic.